mRNA delivery of a class 1/4 SARS-CoV-2 neutralizing antibody protects against diverse sarbecoviruses in a lethal mouse challenge model - Ashwin N. Skelly; Chengcheng Fan; Jennifer R. Keeffe; Arya B. Ökten; Edem Gavor; Maddy L. Newby; Joel D. Allen; Edward F. Kreider; Wenge Ding; Rebecca A. Osbaldeston; Younghoon Park; Andrew J. Connell; et al. (Proceedings of the National Academy of Sciences, 2026)
The unyielding antigenic drift of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), as well as the threat of future zoonotic sarbecovirus spillovers, has prompted the search for broadly neutralizing antibodies (bNAbs) to inform rational therapeutic and vaccine design. Here, we isolated and characterized 20 receptor binding domain (RBD)-directed bNAb lineages from a serially sampled SARS-CoV-2 patient who was infected and vaccinated during the early months of the pandemic. Thirteen of these targeted the highly conserved, cryptic class 1/4 or class 4 RBD epitopes and had long (18 to 26 amino acid) heavy chain complementarity determining region 3 loops that utilized the IGHD3-22 gene segment. Five bNAbs potently neutralized all 18 viruses in a panel containing SARS-CoV-2 variants up to the recently emerged XBB.1.5 and JN.1 strains as well as diverse sarbecoviruses from other clades. Structural analyses of the Ab401 and Ab568 bNAbs complexed with RBD and Spike trimer, respectively, revealed recognition features in common with other class 1/4 bNAbs. Prophylactic administration of Ab401 as a recombinant protein afforded robust protection against infectious challenge with either SARS-CoV-2_WA1 or a related bat sarbecovirus with zoonotic potential. A similar level of protection was achieved when the heavy and light chains of Ab401 were delivered as lipid nanoparticle-encapsulated mRNAs. These data expand the arsenal of SARS-CoV-2 bNAbs for clinical development and identify mRNA-based antibody delivery as a promising platform for both pandemic preparedness and protection of immunocompromised patients against emerging sarbecovirus variants.